HUMANISTIC APPROACH TO LEARNING TO DEVELOP STUDENT POTENTIAL - larasena sena (Teaching and General Education Studies, 2026)
The humanistic approach is one of the learning approaches that emphasizes the holistic development of human potential. This approach places students as the center of the learning process while considering intellectual, emotional, social, and moral development. The purpose of this article is to review the humanistic approach in learning, including its description, advantages, disadvantages, and comparisons with other learning approaches. The method used in this article is a literature review by analyzing various relevant scientific sources. The results show that the humanistic approach can improve students’ motivation, participation, creativity, and social skills. However, this approach also has several limitations such as requiring more time, demanding high teacher competence, and being difficult to apply in large classrooms. Therefore, proper planning is necessary so that the implementation of the humanistic approach can achieve optimal learning outcomes.